Temeljna načela dednega prava - Zupančič, Karel (Pravni letopis, 2008)
The principles of inheritance express legally-political evaluation in law of inheritance; their implementation is partially assured also by the constitution. The author argues that in our law there are only two of these principles: the freedom of testamentary disposition (testamentary freedom) and the principle of family inheritance. The first principle means that with a testament the deceased person can decide on the destiny of his property in a case of death without taking into consideration the legal order of inheritance. The testamentary freedom is limited by law; the strongest contentlimitation is the compulsory portion. Following the second principle, the property of the deceased goes over to persons that are in familial connection with him, provided he did not made different testamentary dispositions. The author's opinion is that the universal succession is not a principle as such but only the expression of legally-technical decision of a legislator. In this article the author lists arguments against the notion that at some other solutions of law of inheritance we are also confronted with principles and he deals with the two mentioned principles more in detail.
Keywords: dedno pravo; dedovanje; Trusts and estates